Morphological, optical, and Raman characteristics of ZnO nanoflakes prepared via a sol-gel method - Mohammad, Kashif; Syed Muhammad, Usman Ali; Mohamed A, Mohd Ali; Abdulgafour, H. I.; Uda, Hashim, Prof. Dr.; Willander, Magnus; Zainuriah, Hassan (WILEY-VCH Verlag GmbH & Co., 2012)
Link to publisher's homepage at http://onlinelibrary.wiley.com